Three Approaches to the Sociological Study of the Social Well-being - Trotsuk, Irina V. (Sociološki pregled, 2019)
The globalizing and diversifying world demands from sociology to constantly redefine its boundaries, especially with psychology. It is also necessary to identify the specifics of the sociological interest to such a psychological issue as mental health. This can be done by limiting the focus of the sociological study to the social well-being that can be ‘measured’ in three perspectives: first, identification of value orientations; second, description of fears that prevail in society or its particular groups; and, third, attempts to measure the level of happiness, its factors and components in terms of their ‘size’, changes and sustainability at the national level and in the comparative perspective. The article presents some empirical examples of all three sociological ‘dimensions’ of the social wellbeing.